1995
DOI: 10.1080/00140139508925263
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of signal word and colour on warning labels: differences in perceived hazard and behavioural compliance

Abstract: Previous research has examined the connoted hazard of various colour and signal words separately. The purpose of the present research was to examine the interaction of signal words and colours. Two separate experiments examined the influence of colour on perceptions of hazard and on compliance to printed warnings. In experiment 1, a sample of 30 undergraduates rated the perceived hazard of signal words printed in specific hazard colours. Results indicated that the level of hazard varied as a function of the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(83 citation statements)
references
References 18 publications
5
77
1
Order By: Relevance
“…Two recent studies by Kalsher et al (1995) and also included the term DEADLY and found that this word connoted a greater degree of hazard than DANGER, confirming earlier results obtained by Wogalter and Silver (1990). Other reports have noted similar results (Braun et al, 1994;Braun and Silver, 1995;Edworthy and Adams, 1996;Taveira et al, 1995).…”
Section: Introductionsupporting
confidence: 59%
“…Two recent studies by Kalsher et al (1995) and also included the term DEADLY and found that this word connoted a greater degree of hazard than DANGER, confirming earlier results obtained by Wogalter and Silver (1990). Other reports have noted similar results (Braun et al, 1994;Braun and Silver, 1995;Edworthy and Adams, 1996;Taveira et al, 1995).…”
Section: Introductionsupporting
confidence: 59%
“…Many studies of signal words and their associated panels for warning design for western nations have been reported (Braun, Kennedy, & Silver, 1994;Braun & Silver, 1995;Bresnahan & Bryk, 1975;Chapanis, 1994;Kline, Braun, Peterson, & Silver, 1993;Leonard, Karnes, & Schneider, 1988;Tajima, Asao, Hill, & Leonard, 1991;Wogalter & Silver, 1990, 1995aYoung, 1998). It is clear from the results that signal words differ in their ability to convey hazard information.…”
Section: Introductionmentioning
confidence: 96%
“…For example, Adams and Edworthy 19 demonstrated an interaction between signal word and color, font size, and border width with regard to perceived hazard. Likewise, Braun and Silver 15 reported a statistically significant interaction between signal word and color. Participants rated 21 words across 5 colors in terms of perceived hazard.…”
Section: Interaction With Signal Wordmentioning
confidence: 90%
“…Indeed, in terms of perceived hazard, Braun and Silver 15 found that red and orange had a higher perceived hazard level than black, green, or blue. Although red was significantly higher than orange, there was no statistically significant difference among black, green, or blue with regard to perceived hazard level.…”
Section: Colormentioning
confidence: 99%